ADHD Medication : Does it Work and is it Safe? - Karniski, Walt, 1950- (Lanham, Maryland : Rowman & Littlefield, 2022)
"This book evaluates the benefits and concerns of using medications to treat children with ADHD, while offering a guide to the different medications themselves"--
Includes bibliographical references and index.
Keywords: Attention-deficit-disordered children; Attention-deficit-disordered children -- Treatment; Attention-deficit-disordered children -- Counseling of